Occurrence of intermediate bifurcational ridges and attached cementicles on furcation area of Iraqi mandibular molars (Mustansiria Dental Journal, 2018)
Successful treatment of molar furcation defects remains a challenge in clinicalpractice. Knowledge of anatomic factors facilitates predictable management offurcation involvement lesions. Intermediate bifurcational ridge (IBRs) andcementicles are of those anatomical variations which considered as problems inprogression treatment of the disease.The present study was carried out to investigate the prevalence of IBRs andcementicles in Iraqi mandibular molars. The sample used in the study included 498extracted mandibular molars. The results revealed that the prevalence IBRs was306/498 teeth (61.44%), and that for the cementicles was 204/498 teeth (40.96%).The total sample was allocated into two groups:Group 1 included 313 molars (165 mandibular first molar and 148 mandibularsecond molar) , The teeth of group 1 were extracted because of caries andpulpal lesions, whileGroup 2 included 185 mandibular molars ( 98 first molar and 87 second molar).The reason of extraction of the teeth of group 2 was periodontal disease (differentdegrees of furcation involvement). For group 1 the results showed that 111/313(35.46%) of mandibular molars had attached cementicles in furcation area and185/313 (59.10%) were affected by IBRs. While in group 2 the percentage of bothanomalies was higher than that of group 1. In group 2 the results revealed that 93/185(50.27%) of the teeth had cementicles and 121/185 (65.4%) were recorded withIBRs.These results give an indication that the prevalence of cem. and IBRs highenough to be of clinical importance.